Adjustment to acute or early HIV-1 infection diagnosis to prompt linkage to care and ART initiation: qualitative insights from coastal Kenya - van Der Elst, E; Kombo, B; Mugo, P; Thiong'O, A; Kanungi, J; Wahome, E; Chirro, O; Graham, S; Operario, D; Sanders, E (Routledge, 2018)
Diagnosing and treating patients with acute or early HIV-1 infection (AEHI) is an important strategy to prevent HIV-1 transmission. We used qualitative methods to understand factors that facilitate adjustment to AEHI diagnosis, prompt linkage to care and initiation of antiretroviral treatment (ART). Twenty-three AEHI patients (12 women, 11 men) included 18 participants identified at health facilities, and 5 participants identified in a sex worker cohort. Of these, 17 participants (9 women, 8 men) participated in qualitative interviews about their AEHI status 2 weeks after diagnosis. Thirteen participants (7 women, 6 men) returned for a second interview 12 weeks after diagnosis. Interviews explored participants' experiences at the time of and following their diagnosis, and examined perceptions about ART initiation and behavior change recommendations, including disclosure and partner notification. A grounded theory framework was used for analysis, eliciting three important needs that should be addressed for AEHI patients: 1) the need to better understand AEHI and accept one's status; 2) the need to develop healthy strategies and adjust to the reality of AEHI status; and 3) the need to protect self and others through ART initiation, adherence, safer sex, and disclosure. A preliminary conceptual framework to guide further intervention and research with AEHI populations is proposed.